Fly meets yeast: checking the correct orientation of cell division - Pereira, Gislene; Yamashita, Yukiko (Trends in cell biology, 2011)
Cell division is generally thought to be a process that produces an exact copy of the mother cell by precisely replicating its genomic DNA, doubling organelles, and segregating them into two cells. Many cell types from bacteria to human cells divide asymmetrically, however, to generate daughter cells with distinct characteristics. Such asymmetric divisions are fundamental to the lifespan of a cell, to embryonic development, and to stem cell homeostasis. Asymmetric division requires coordination of cellular asymmetry and the cell division machinery. Accumulating evidence suggests that the basic molecular mechanisms that govern this process are conserved from yeast to humans. In this review we highlight similarities in the mechanisms of asymmetric cell division in yeast and Drosophila male germline stem cells (GSCs) in the hope of extracting common themes underlying several systems.
Gesehen am 15.05.2017